Mitigation of climate change and environmental hazards in plants: Potential role of the beneficial metalloid silicon - Bokor, Boris; Santos, Carla S.; Kostoláni, Dominik; Machado, Joana; da Silva, Marta Nunes; Carvalho, Susana M.P.; Vaculík, Marek; Vasconcelos, Marta W. (Journal of hazardous materials, 2021)
In the last decades, the concentration of atmospheric CO2 and the average temperature have been increasing, and this trend is expected to become more severe in the near future. Additionally, environmental stresses including drought, salinity, UV-radiation, heavy metals, and toxic elements exposure represent a threat for ecosystems and agriculture. Climate and environmental changes negatively affect plant growth, biomass and yield production, and also enhance plant susceptibility to pests and diseases. Silicon (Si), as a beneficial element for plants, is involved in plant tolerance and/or resistance to various abiotic and biotic stresses. The beneficial role of Si has been shown in various plant species and its accumulation relies on the root's uptake capacity. However, Si uptake in plants depends on many biogeochemical factors that may be substantially altered in the future, affecting its functional role in plant protection. At present, it is not clear whether Si accumulation in plants will be positively or negatively affected by changing climate and environmental conditions. In this review, we focused on Si interaction with the most important factors of global change and environmental hazards in plants, discussing the potential role of its application as an alleviation strategy for climate and environmental hazards based on current knowledge. [Display omitted] •Climate changes and environmental hazards are predicted to be worsen in the future.•Plant growth, biomass and yield production is negatively affected by climate and environmental stresses.•Si application seems to be a promising alleviation strategy for mitigating climate and environmental stresses on crops.